Program Usaha Kesehatan Sekolah: Upaya Kolaboratif Untuk Kesehatan Anak - Nurochim Nurochim; Siti Ngaisah Nurochim (Universitas Negeri Medan, 2020)
This article aims to examine the importance of school-based health promotion as an effort to improve children's health. To improve children's health through school institutions, a policy guideline that is guided by them is needed. Institutional theory is used in this article to describe how efforts to improve student health. Literature relating to students' health conditions and the implementation of health promotion is used as a database in this article. Furthermore, the data from various literatures were analyzed qualitatively based on the study group. It can be concluded that health promotion to improve the quality of health can be carried out through the School Health Promotion. Management with a Joint Regulatio of 4 (four) Ministers, namely the Ministry of Education and Culture; Ministry of Religion, Ministry of Health, and Ministry of Home Affairs. The joint regulation is one of the strengths in institutionalizing programs, namely rules or policies. Policies on school-based health education provide detailed guidance, so that actors can act systematically. With systematic action it can influence social networking and cross-sectoral coordination.